Antiviral Therapeutic Monitoring: Role of Hepatitis C Virus Core Antigen versus Hepatitis C Virus RNA by Polymerase Chain Reaction - Farooq, Hajra; Iqbal, Muhammad Zaheer; Zamaan Tariq, Waheed U; Chughtai, Omar Rasheed; Choudhry, Asad Ali; Mushtaq, Saadiya (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study the association between hepatitis C virus viral load by real-time PCR and core antigen value of HCV and define an antiviral treatment monitoring cut-off value for HCV core antigen. Study Design: Cross-sectional validation study. Place and Duration of Study: Department of Infectious Diseases, Chughtai Lab Lahore Pakistan, from Jun 2017 to Mar 2018. Methodology: To establish the association between these two parameters, we took a hundred positive plasma samples for HCV RNA and subjected them to an HCV Core antigen test. Furthermore, the samples were divided into three categories based on their viral load; <2000 IU/ml, 2000-10,000 IU/ml and >10000 IU/ml. Results: Our results showed that the hepatitis C virus core antigen was concordant with hepatitis C virus RNA by PCR when the viral load was above 2000 IU/ml. Below the HCV RNA load of 2000 IU/ml, the HCV core antigen had a sensitivity of 94.95% and specificity of 88.89%. Conclusion: In patients having a viral load above 2,000 IU/ml, the hepatitis C virus core antigen value can be used as a marker for diagnosis and monitoring antiviral therapy. After the antiviral treatment, HCV RNA real-time PCR should be performed to validate viral clearance.